Social learning in the caracara chimango, milvago chimango (aves: Falconiformes): An age comparison - Biondi, Laura Marina (2010)
Milvago chimango is a gregarious raptor showing great ecological plasticity. Their ability to explore new resources has allowed them to survive in areas with increasing human modification. In this study, we evaluated the social learning ability in wild‐caught individuals of M. chimango. In particular, we tested whether an ‘observer’ individual could improve the acquisition of a novel behaviour by watching a ‘demonstrator,’ and we examined the effects of age of both observers and demonstrators on social learning. We measured the ability of 18 observers to open an opaque Plexiglas box containing food, and we compared their performance to that of 10 control birds who did not watch a demonstrator solve the task. Prior to watching a demonstrator, only two of the observers and two of the control birds were able to open the box. After watching a demonstrator, 67% of observers were able to open the box, outperforming control birds in speed and success. Juvenile observers were more successful and faster than adults at contacting and opening the box. The age of the demonstrator did not influence the observers’ likelihood of success. These results showed that M. chimango are able to learn a box‐opening task with a hidden food reward by observing the behaviour of a conspecific and that this behaviour persisted over several days. Social learning ability in M. chimango might allow certain behavioural patterns, such as those related to novel resource acquisition in modified environments, to be socially transmitted among individuals in a population.